The Title ḥꜢ.ty-Ꜥ.w ḥꜢ ı ͗nb.w n.w Ptḥ, “Mayor of Beyond the Walls of Ptah”, and Early 19th Dynasty Temple Building at Memphis - Staring, Nico (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
The Mayor of Memphis was a key player in the administration of Egypt’s capital. Despite that prominent position, we do not know much about the official’s duties. The recent identification of a photograph taken by Egyptologist Théodule Devéria in 1859, which features a doorway in the long-lost superstructure of the tomb of the Mayor Ptahmose, has added valuable new data to the subject. Texts on the structure’s two door jambs record a selection of his titles. One of these, ḥ Ꜣ .ty- Ꜥ .w ḥ Ꜣ ı ͗nb.w n.w Ptḥ , “Mayor of beyond the walls of Ptah”, is not known from any other sources. This paper proposes an interpretation of this title, which also requires a re-evaluation of the office of Mayor of Memphis at the very beginning of the 19th Dynasty. The administration of town and temple are studied using prosopographical data as a primary source, with special emphasis on the construction works in and around ı ͗nb.w , “Walls”.